Mediation of Resilience in the Association Between Personality Traits and Suicidal Ideation Among Chinese Adolescents - Che, Yusan; Fang, Die; Cai, Le; Ran, Hailiang; Chen, Lin; Wang, Sifan; Peng, Junwei; Sun, Hao; Liang, Xuemeng; Xiao, Yuanyuan (Frontiers in Psychology, 2022)
The positive connection between personality traits and suicidal ideation (SI) has been established. However, the possible mediation of resilience within this association has never been thoroughly discussed. In the present study, we aimed to investigate this topic by using a population-based cross-sectional survey data of 4,489 Chinese children and adolescents. Self-administered questionnaire was used to collect information from the participants. Univariate and multivariate Logistic regression models were adopted to measure the crude and adjusted associations between personality traits, SI, and resilience. Path analysis was performed to evaluate the mediation of resilience in the association between personality traits and SI. For 4,489 study subjects, mean of age was 13.4 years, ethnic minorities accounted for 71.8%, and over a half (54.6%) were middle school students. The reported prevalence rates for one-week, one-year, and lifetime SI were 27.6% (95% CI: 24.9%, 30.0%), 35.5% (95% CI: 30.8%, 41.0%), and 56.7% (95% CI: 52.3%, 61.0%), respectively. Girls reported significantly higher prevalence of SI than boys. Path analysis results revealed a prominent mediation of resilience, moreover, for different dimensions of personality traits, the proportion of mediation by resilience varied. Our major findings suggest that resilience-based intervention measures could be considered in preventing personality traits related suicidal risk among youngsters. For children and adolescents, the measuring of personality dimensions may also be helpful in targeting key subpopulations of intervention priority.